Retained earnings, foreign portfolio ownership, and the German current account: A firm-level approach - Stefan Goldbach; Philipp Harms; Axel Jochem; Volker Nitsch; Alfons J. Weichenrieder (Technische Universität Darmstadt, Department of Law and Economics, 2024)
In some countries, a sizable fraction of savings is derived from corporate savings. Although larger, traded corporations are often co-owned by foreign portfolio investors, current international accounting standards allocate all corporate savings to the host country. This paper suggests a framework to correct for this misleading attribution and applies this concept to Germany. For the years 2012 to 2020, our corrections retrospectively reduce German savings and consequently the German current account surplus by, on average, exteuro11.5bn annually. This amounts to lowering Germany's average official current account surplus ( exteuro226.6bn) across these years by approximately five percent.
urn:nbn:de:tuda-tuprints-274680
Keywords: F32; E21; 330; current account; balance of payments; corporate savings; retained earnings; foreign portfolio investment; Germany